2011 IEEE/ACM Second International Conference on Cyber-Physical Systems 2011
DOI: 10.1109/iccps.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring in Wireless Sensor Networks by the Embedded Goertzel Algorithm

Abstract: Abstract-Structural health monitoring aims to provide an accurate diagnosis of the condition of civil infrastructures during their life-span by analyzing data collected by sensors. To this purpose, detection and localization of damages are fundamental tasks. This paper introduces a wireless sensor network for structural damage detection and localization in which the sensor nodes, in order to estimate the energies of specific frequency bands, process the acceleration data locally in real-time using the Goertzel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…It was previously demonstrated in [10], [11], [12], that a network of wireless accelerometers can save considerable amount of resources by monitoring only small part of the vibration spectrum, but no solutions on the selection problem were proposed.…”
Section: A Structural Health Monitoringmentioning
confidence: 99%
“…It was previously demonstrated in [10], [11], [12], that a network of wireless accelerometers can save considerable amount of resources by monitoring only small part of the vibration spectrum, but no solutions on the selection problem were proposed.…”
Section: A Structural Health Monitoringmentioning
confidence: 99%
“…This allows expanding analysis coverage and repeating inspections to validate and improve the desperately needed deterioration models. Research effort has been investigated into applying the versatility of multi-modal multi-sensor systems to the civil domain in a cyber-physical approach [7], [17]. Sensor systems or motes are developed in favor of the low-cost, availability, sensor versatility and time-to-market.…”
Section: E Data Fusion and System Impactmentioning
confidence: 99%
“…So the neural network algorithm can be applied to the WSN to achieve data fusion. Some related research results have been reported in recent years [3][4][5]. The proposed algorithm takes the data fusion technology to the routing layer of the WSN, Based on hierarchical routing, a new data fusion algorithm based on wavelet neural network (WNNDFA) was proposed.…”
Section: Introductionmentioning
confidence: 99%